2021
DOI: 10.1109/jstars.2021.3105582
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Spatial Heterogeneity of Land Surface Temperature in Nanjing, China

Abstract: The environment and climate significantly affect the land surface temperature (LST) of a city. Previous studies have revealed that LST exhibits significant spatial heterogeneity primarily caused by a combination of natural factors and human activities. Based on this, the introduction of point of interest data of the "production-living-ecological space" divides the influencing pattern into a comprehensive description of human activities supplemented by natural factors, resulting in the precise influencing facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This may imply the high importance scores of the LUCC in both model results. Although the DEM greatly influenced the modeling process, as has been reported in previous studies [ 56 ], the importance of the LUCC represents a more significant impact than that of the DEM in the models assessed in this study. This result may be due to the flat terrain and abundant plains in the study area.…”
Section: Discussionmentioning
confidence: 61%
“…This may imply the high importance scores of the LUCC in both model results. Although the DEM greatly influenced the modeling process, as has been reported in previous studies [ 56 ], the importance of the LUCC represents a more significant impact than that of the DEM in the models assessed in this study. This result may be due to the flat terrain and abundant plains in the study area.…”
Section: Discussionmentioning
confidence: 61%
“…During the transformation, the urban microclimate and landscape ecological risks significantly changed, which affected urban development, the ecological environment and the well-being of human life. The previous literature has shown that landscape ecological risk and LST are associated with road distance [25,33], urban expansion [34][35][36][37], climate change and human activities [38][39][40]. However, mitigating effects on both factors have also been identified that are merely related to their own inherent qualities.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, most of the RSEI index extraction uses LandSAT data with a spatial resolution of 30 meters for index extraction [57], [58]. Although the spatial resolution of LandSAT data is high, its temporal resolution is low, but it is difficult to obtain complete data images of the same date in the mesoscale urban study area, so only images of similar dates and the same time period can be used for stitching and cropping.…”
Section: A Effects Of Aisf and Population Distribution On The Ecologi...mentioning
confidence: 99%